Pengembangan Kemasan Inovatif Susu Kambing Bumdes Desa Lalang Sembawa untuk Meningkatkan Nilai Jual Produk Lokal: Pengabdian - Rike Rahayu; Eka Putri Dwitami; Nandhita Salzabilla; Vegita Julianda; Susi Hildayanti; Emilda; Muhammad Wadud (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community-Owned Enterprises (BUMDes) in Desa Lalang Sembawa face challenges in marketing and digitalization, limiting the potential of local goat milk products. This study aims to develop innovative packaging and digital marketing strategies to increase product value and market reach. The research uses a qualitative community service approach with direct mentoring to empower goat milk UMKM actors. The population includes all BUMDes managers of "Mugi Langgeng Farm," with purposive sampling selecting key managers and consumers. Instruments include field observation, in-depth interviews, and participatory discussions. Data were analyzed thematically with a descriptive approach. Results show the creation of a locally representative, visually attractive packaging design combined with effective Google My Business utilization, enhancing product visibility and consumer trust. The introduction of informative labels strengthened brand identity. The conclusion highlights that integrating innovative packaging with digital marketing tools significantly improves the competitiveness and sustainability of local UMKM products. Continued mentoring is needed to optimize digital adoption.